Food additives electronic handbook - Ash, Michael; Ash, Irene (Hampshire : Gower, 1995)
This electronic handbook contains nineteen indexes
Intel 386SX CPU, EGA adapter, 2MB RAM, 20MB of free hard disk space, Windows 3.0 or 3.1 or higher in standard mode
Keywords: Food addtives